Distribution of Hammerhead and Hammerhead-like RNA Motifs Through the GenBank - Ferbeyre, Gerardo; Bourdeau, Véronique; Pageau, Marie; Miramontes, Pedro; Cedergren, Robert (Genome Research, 2000)
Hammerhead ribozymes previously were found in satellite RNAs from plant viroids and in repetitive DNA from certain species of newts and schistosomes. To determine if this catalytic RNA motif has a wider distribution, we decided to scrutinize the GenBank database for RNAs that contain hammerhead or hammerhead-like motifs. The search shows a widespread distribution of this kind of RNA motif in different sequences suggesting that they might have a more general role in RNA biology. The frequency of the hammerhead motif is half of that expected from a random distribution, but this fact comes from the low CpG representation in vertebrate sequences and the bias of the GenBank for those sequences. Intriguing motifs include those found in several families of repetitive sequences, in the satellite RNA from the carrot red leaf luteovirus, in plant viruses like the spinach latent virus and the elm mottle virus, in animal viruses like the hepatitis E virus and the caprine encephalitis virus, and in mRNAs such as those coding for cytochrome P450 oxidoreductase in the rat and the hamster.